Respuesta :
-5(p+3/5) = -4
First you have do distributive multiplication.
-5(p) -5(3/5) = -4
-5p -3 = -4
Then, group like terms and change its sign.
-5p = -4 + 3
-5p = -1
To get p, we need to divide both sides by -5. Both numbers have negative signs, it cancels each other.
-5p / -5 = -1/-5
p = 1/5
To check: p = 1/5
-5(p+3/5) = -4
-5(1/5 + 3/5) = -4
-5(4/5) = -4
-20/5 = -4
-4 = -4
First you have do distributive multiplication.
-5(p) -5(3/5) = -4
-5p -3 = -4
Then, group like terms and change its sign.
-5p = -4 + 3
-5p = -1
To get p, we need to divide both sides by -5. Both numbers have negative signs, it cancels each other.
-5p / -5 = -1/-5
p = 1/5
To check: p = 1/5
-5(p+3/5) = -4
-5(1/5 + 3/5) = -4
-5(4/5) = -4
-20/5 = -4
-4 = -4
Hi there!
Let us rewrite the equation, the same exact way you asked it. :)
-5(p+3/5)=-4
Step 1) Simplify both sides of the equation.
(-5) (p) + (-5) (3/5) = -4
-5p + -3 = -4
-5p - 3 = -4
Step 2) Add 3 to both sides.
-5p + - 3 + 3 = -4 + 3
-5p = -1
Step 3) Divide both sides by -5.
-5p/-5 = -1/-5
p = 1/5
Final Answer -
p = 1/5, 0.2, or 20%
Hope this helps!
All the /'s were for fraction bars. :)